2019
DOI: 10.1017/s0022149x19000130
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of hookworm isolates from stray dogs, humans and selected wildlife from South Africa

Abstract: There is a paucity of information on hookworm species in humans, domestic animals and wildlife in southern Africa. Our study aimed to identify hookworm species from stray dogs, humans, and selected wildlife from South Africa. A total of 356 faecal samples were screened for the presence of hookworm-like eggs and subsequently coproculture from the positive samples was carried out to obtain larvae. Hookworm-like eggs were detected in 23.03% (82/356) of samples. Of these samples, 78/296 were from dogs, 3/50 from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
(90 reference statements)
1
26
0
Order By: Relevance
“…Humans infected percutaneously may develop cutaneous larva migrans (CLM) [35]. Cases of eosinophilic enteritis [36], as well as patent infections have also been described [37].…”
Section: Introductionmentioning
confidence: 99%
“…Humans infected percutaneously may develop cutaneous larva migrans (CLM) [35]. Cases of eosinophilic enteritis [36], as well as patent infections have also been described [37].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, cases of CLM could be treated fairly easily using topical anthelmintics (Heukelbach and Feldmeier, 2008); however, such treatments will not be effective against MDR worms. Cases of eosinophilic enteritis (Prociv and Croese, 1996), as well as patent infections have also been described (Ngcamphalala et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of the study included the following: (a) no clinical samples were collected to confirm whether the organisms isolated have been associated with infections caused in humans; (b) not all the samples could be sequenced due to a very limited budget for molecular studies and sequencing; and (c) many of the samples also contained hookworms and rotifers and could not be further assessed. Several studies have shown that hookworms are present in the faeces of livestock [ 185 ] and domestic animals [ 186 ], and therefore, the eggs could have entered underground aquifers, while several reports on the prevalence of rotifers in groundwater have been published [ 187 , 188 ]. Hence, more studies are needed to determine the health risk to vulnerable individuals drinking water containing these organisms and the effectiveness of point-of-use devices in eliminating them.…”
Section: Discussionmentioning
confidence: 99%